Exploring the association between mild behavioral impairment and plasma p‐tau217: Implications for early detection of Alzheimer's disease - Maryam Ghahremani; Rebeca Leon; Eric E. Smith; Zahinoor Ismail (Alzheimer’s & Dementia: Diagnosis, Assessment & Disease Monitoring, 2025)
Abstract INTRODUCTION Mild behavioral impairment (MBI), marked by late‐onset persistent neuropsychiatric symptoms (NPS), may signal early dementia risk. While MBI is linked to previously established amyloid‐beta (Aβ) and tau biomarkers, its association with plasma p‐tau217, a promising blood‐based biomarker for Alzheimer's disease (AD), remains unexplored. Here, we investigated the association between MBI and plasma p‐tau217 in dementia‐free individuals from the Alzheimer's Disease Neuroimaging Initiative. METHODS MBI was defined using the Neuropsychiatric Inventory (NPI) data. Linear regression assessed the association between NPS status and continuous p‐tau217 levels, while logistic regression modeled the association between NPS status and p‐tau217 positivity, using a study‐specific cutoff. Models adjusted for age, sex, education, and cognitive diagnosis. RESULTS Among 101 participants (mean age = 72.0 ± 6.5; 44.6% female), those with MBI had higher plasma p‐tau217 levels (β = 36.4%; 95% confidence interval [CI]: 2.2–82.0, p = 0.04) and higher odds of being p‐tau217 positive (odds ratio [OR] = 3.06, 95% CI: 1.14–8.70, p = 0.03) than MBI‐ participants. DISCUSSION Findings support the role of MBI in AD risk stratification. Highlights Mild behavioral impairment (MBI) is linked to elevated plasma p‐tau217, a specific Alzheimer's disease biomarker. MBI increases the odds of plasma p‐tau217 positivity in dementia‐free individuals. Findings support MBI as an early indicator for Alzheimer's disease risk. MBI assessment can improve biomarker‐based screening and clinical trial efficiency.